Superconductors New Developments - Gabovich, Alexander (IntechOpen, 2015)
The chapters included in the book describe recent developments in the field of superconductivity. The book deals with both the experiment and the theory. Superconducting and normal-state properties are studied by various methods. The authors presented investigations of traditional and new materials. In particular, studies of oxides, pnictides, chalcogenides and intermetallic compounds are included. The superconducting order parameter symmetry is discussed and consequences of its actual non-conventional symmetry are studied. Impurity and tunneling effects (both quasiparticle and Josephson ones) are among topics covered in the chapters. Special attention is paid to the competition between superconductivity and other instabilities, which lead to the Fermi surface gapping.